Sustainable Development for Food Waste: A Case Study of Catered Meal Service at Schools and Elderly Care Homes - Barth, Henrik; Bäckman, Emma; Ellmarker, Josefin (Journal of Strategic Innovation and Sustainability, 2019)
Food waste is an important topic in the context of sustainable development. Although many studies have addressed this topic, there is still limited knowledge owing to insufficient data. This study reports on food waste in two institutional settings in a Swedish municipality: schools and elderly care homes. The findings suggest it is easier to measure and reduce food waste in stable environments, such as exist at schools, than at environments characterized by change and unpredictability, such as exist at elderly care homes. Specific areas examined and compared include cooking and receiving kitchens, infrastructure, communications, and support.